Study on the Making of Blended Cement by Mixing Granulated Blast Furnace Slag with Portland Cement Clinker - Arief Sudarsono; Kris M. Kosasih (Institute for Research and Community Services (LPPM) ITB, 2000)
Abstract. This paper presents the results of laboratory into the effect of slag fineness and slag composition added to portland cement clinker, to the compressive strength of the paste. The results showed that slag of 4260 cm2/gram fineness can be added up to 3O% to a portland cement clinker to increase compressive strength from 28 MPa to about 40 MPa. Scanning electron micrograph of the pastes showed that the inter granular voids between slag particles and sand particles were densely filled with line CaO-SiO2-H2O gel after 28 days observation, and in case clinker without slag, densification of CaO-SiO2-H2O gel still left pores even after 23 days of observation. The fineness of slag is more important than its composition in the blended cement. Studi Pembuatan Semen Campur (Blended Cement) dari Campuran Terak Tanur Tiup dan Klinker Semen PortlandSari. Paper ini menyajikan hasil percobaan laboratorium yang meneliti pengeruh kehalusan terak dan komposisi terak yang ditambahkan ke dalam klinker semen Portland. Hasil percobaan menunjukkan bahwa terak dengan kehalusan 4260 cm2/gram dapat ditambahkan ke dalam klinker sampai maksimum 30%, untuk meningkatkan kuat tekan dari semula 28 Mpa menjadi 40 Mpa. Foro SEM menunjukkan bahwa kekosongan antarbutir partikel terak dengan partikel pasir terisi dengan baik oleh pasta halus CaO-SiO2-H2O setelah pengamatan selama 28 hari. Untuk klinker tanpa terak, pasta masih mempunyai pori mesipun setelah 28 hari pengamatan. Kehalusan terak lebih penting daripada komposisinya di dalam semen campur.